2017
DOI: 10.1002/car.2449
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Risk, Individualised Responses: An Assessment of Safeguarding Responses to Nine Cases of Peer‐on‐Peer Abuse

Abstract: Practitioners, academics and policymakers are increasingly questioning the sufficiency of safeguarding practice in protecting young people from peer-on-peer abuse in England. Using the findings from an in-depth analysis of nine cases where young people either raped or murdered their peers, this article explores approaches to assessing and intervening with those affected by peer-on-peer abuse. Building upon international calls for a contextual account of abuse between young people, the article identifies a prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 13 publications
3
46
0
Order By: Relevance
“…A recent review of peer‐on‐peer abuse files revealed data available on 145 young people. Of these, only 1.4 per cent had recorded evidence of contact with sexual health services (Firimin, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of peer‐on‐peer abuse files revealed data available on 145 young people. Of these, only 1.4 per cent had recorded evidence of contact with sexual health services (Firimin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our next two papers explore different aspects of peer‐on‐peer abuse and exploitation, and highlight further disconnects in our approaches to safeguarding children and young people. Carlene Firmin () from Bedfordshire (another Child Abuse Review author who will be presenting at the BASPCAN international congress) has used case review methodology to examine the police records of investigations into nine cases of extreme peer‐on‐peer abuse (murder or multiple rape). In her study, Firmin identified a significant disconnect between the very individualised and family‐focused response of child protection agencies and the realities of the social and environmental contexts within which peer‐on‐peer abuse occurs.…”
Section: Peer‐on‐peer Abuse and Exploitationmentioning
confidence: 99%
“…She found that investigations concentrated on the behaviour of individuals and parental capacity to protect their children and failed to explore the contexts within which the young people had actually been abused. As a result,
‘Assessments focused on the ability of young people, and their families, to avoid abusive peer groups, schools or neighbourhoods, rather than the ability of professionals to make those environments safer.’ (Firmin, , p. 49)
…”
Section: Peer‐on‐peer Abuse and Exploitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people also encounter sexual violence in public contexts (Firmin, ; Hackett, ; Smallbone and others, ). Young people have been sexually exploited in parks, shopping centres, fast food restaurants and hotels.…”
Section: Introductionmentioning
confidence: 99%